Significance of the Platelet Indices as a Severity Marker of Severe Preeclampsia - عبد الرحمن, أحمد; رمضان, لينا; رستم حج علي, فرهاد (Latakia University Journal -Medical Sciences Series, 2020)
Background: Platelet parameters alterations are one of the most commonly identified hematological changes in preeclampsia. Aim: The aim of this study was to investigate whether platelet count, mean platelet volume (MPV) and platelet distribution width (PDW) could predict severe form of preeclampsia. Materials and Methods: This was a case - control study carried out at Department of Obstetrics and Gynecology Tishreen university Hospital, Lattakia, Syria, from January 2019 to January 2020. Ninety pregnant women with singleton pregnancy were recruited and divided into 2 groups; normal pregnant women (n =40) as a control group and women with severe preeclampsia (n=50). Blood samples were recruited upon and analyzed for platelet indices; platelet count, mean platelet volume (MPV) and platelet width diameter (PWD) by automated hematology analyzer. The receiver-operating characteristic (ROC) curves of these indices were generated and the predictive values of the selected potential parameters were examined. P-Value ≤ 0.05 was considered significant. Results: Platelet count was significantly lower in women with severe preeclampsia compared to normal pregnant women groups (190±68.5 vs. 240±60.8 with P˂0.05) respectively. Mean platelet volume and platelet width distribution were significantly higher in women with severe preeclampsia compared to normal pregnant women groups (11.1±1.08 vs. 8.5±0.9 with p˂0.05 for MPV and 17.2±2.13 vs. 11±1.7 with p˂0.05 for PDW) respectively. Conclusion: Due to increased platelet destruction and platelet turnover in patient with severe preeclampsia, decreasing platelet count and increasing MPV and PWD may play a role in predicting preeclampsia. Platelet indices are simple, cheap and practical tools in predicting severity of preeclampsia.